Analisis Visual Cover Majalah Bobo Tahun 2015 - Abdul Rahman Prasetyo; Nila Rahmawati; Ayu Pramudya Kusumanada (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2022)
Bobo Magazine is a special magazine for legendary children in Indonesia. The cover of Bobo Magazine has a strong appeal and character so that it is easily recognized by readers. This study aims to find out in more detail about visual design standards including illustrations, colors, typography, and cover layouts for the 2015 Special Edition of Bobo Magazine. This study uses a descriptive qualitative method. The results showed that on the cover of the 2015 special edition of Bobo magazine, digital illustrations were used with the character of a rabbit personified as a human form. The typography used is Fantasy and San Serif fonts. The colors presented are classified as full color, striking, bright and not gloomy. The layout is positioned asymmetrically but still applies the principles of unity, balance, rhythm, and emphasis. The conclusion of this study is that Bobo has a characteristic in the form of an illustration of a rabbit personified as a human named Bobo who is the main character in each edition. In addition, other characteristics include the shape of the logo/nameplate, the same font in each edition except for the headline. The slogan "Friends to Play and Learn" is also a characteristic found in Bobo Magazine. The colors used are also in accordance with the age of the children who like colorful, striking and bright colors.